Cost per responder for guselkumab versus secukinumab in the United States based on a head-to-head trial of moderate to severe plaque psoriasis. (2nd January 2022) - Teeple, Amanda; Fitzgerald, Timothy
Abstract: Aims: To estimate cost per response (CPR) in the United States and number-needed-to-treat (NNT) among subjects receiving guselkumab or secukinumab for moderate to severe plaque psoriasis. Materials and methods: Results from ECLIPSE, a double-blind, head-to-head, 48-week study of guselkumab compared with secukinumab were used to estimate 48-week, annual induction, and maintenance year CPRs for Psoriasis Area and Severity Index (PASI) 75, 90, and 100 responses for all patients and for PASI 90 response in patients according to previous systemic treatment. Results: Week 48 PASI 90 response rates were 84.5% for guselkumab and 70.0% for secukinumab. The CPR for PASI 90 response at 48 weeks was 89, 960 for guselkumab versus 110, 977 for secukinumab, and for the maintenance year it was 77, 109 for guselkumab versus 88, 781 for secukinumab. The NNT for a PASI 90 response was 1.18 for guselkumab and 1.43 for secukinumab. CPR and NNT values were also lower for guselkumab than for secukinumab, for PASI 75 and PASI 100 for the three time periods, and for PASI 90 at 48-weeks, regardless of previous systemic treatment. Conclusions: Results from a head-to-head study showed that, compared with secukinumab, guselkumab had lower NNTs and CPRs for PASI 75, PASI 90, and PASI 100 responses.